2018
DOI: 10.3389/fpsyg.2018.00382
|View full text |Cite
|
Sign up to set email alerts
|

Explicit Versus Implicit “Halal” Information: Influence of the Halal Label and the Country-of-Origin Information on Product Perceptions in Indonesia

Abstract: Halal refers to what is permissible in traditional Islamic law. Food that meets halal requirements is marked by a halal label on the packaging and should be especially attractive to those Muslims who follow the set of dietary laws outlined in the Quran. This research examines the role of the halal label (explicit cue) and the country-of-origin (COO) (implicit cue) in predicting positive product perceptions among Muslim consumers. We hypothesized that when an explicit sign of “halalness” (i.e., halal label) rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 23 publications
2
33
0
Order By: Relevance
“… Martínez-Ruiz and Gómez-Cantó’s (2016) study emphasizes that using the Internet to seek food service information has now become a common practice among people today. More people than ever before have positive attitudes toward finding information about food online ( Martínez-Ruiz and Gómez-Cantó, 2016 ; Maison et al, 2018 ). Also, people are more likely to search information about food on the Internet than any other product or service ( Hidalgo-Baz et al, 2017 ; Whiley et al, 2017 ; Wong et al, 2018 ).…”
Section: Background Descriptionsmentioning
confidence: 99%
“… Martínez-Ruiz and Gómez-Cantó’s (2016) study emphasizes that using the Internet to seek food service information has now become a common practice among people today. More people than ever before have positive attitudes toward finding information about food online ( Martínez-Ruiz and Gómez-Cantó, 2016 ; Maison et al, 2018 ). Also, people are more likely to search information about food on the Internet than any other product or service ( Hidalgo-Baz et al, 2017 ; Whiley et al, 2017 ; Wong et al, 2018 ).…”
Section: Background Descriptionsmentioning
confidence: 99%
“…Maison, Marchlewska, Syarifah, Zein, and Purba (2018), for example, found that halal labels worsen product perceptions among religious people, when they were presented as produced in nonislamic countries. Maison, Marchlewska, Syarifah, Zein, and Purba (2018), for example, found that halal labels worsen product perceptions among religious people, when they were presented as produced in nonislamic countries.…”
Section: Asymmetric Information and Cognitive Biases In Consumer Chmentioning
confidence: 99%
“…Existing evidence confirms that many different types of FOP labels influence product perceptions. Maison, Marchlewska, Syarifah, Zein, and Purba (2018), for example, found that halal labels worsen product perceptions among religious people, when they were presented as produced in nonislamic countries. Regarding labels that highlight nutritional quality, recent studies suggest that varying the design and context where labels are employed may lead to different-and sometimes, unintended-results.…”
Section: Some Examples Include Different Versions Of Traffic Light Lamentioning
confidence: 99%
“…Hence the need for international companies to identify ways of enhancing the supply and image of the country which are not separated from ethnic-religious precepts and, in the case of Halal certification, to know how to incorporate this in their international marketing strategy. The "Halalness" of the product should also be reinforced in a more explicit way, for example, by using an Arabic name for the product and Arabic letters on the packaging (Maison et al, 2018). However, international companies must identify international marketing strategies capable of exploiting both country image and supply features, integrating ethnic and religious precepts.…”
Section: Managerial Implicationsmentioning
confidence: 99%